Bioimpedance Phase Angle and Muscle Strength Performance in Young Male Volleyball Athletes - Cirillo, Everton Luis Rodrigues (2023)
Volleyball performance depends partially on lower limb strength. The phase angle (PhA) is a marker of functional muscle mass and a surrogate measure of athletic muscle performance. This study aimed to verify the correlation between PhA (bioimpedance) and lower limb muscle strength in young volleyball athletes. The sample included 38 young male volleyball athletes (Age: 16.7±1.3 years; Weight: 73.7±9.7 kg; Height: 179.3±6.9 cm). We performed a cross-sectional observational study and evaluated the volleyball athletes for vertical jump tests (Counter-Movement Jump: CMJ and Squat Jump: SJ) and whole-body bioimpedance. The Pearson test showed positive and moderate significant correlations between the PhA, CMJ, and SJ (r=0.550 and r=0.559, respectively). Our findings demonstrated that assessing the PhA through bioimpedance provides relevant measures of muscle strength and power in young volleyball athletes.